Method for measuring sulfur content in lithium ion battery ternary material
By wrapping the sample of the ternary material of the lithium-ion battery with metal foil and laying the magnetic permeability substance, the problem of incomplete combustion of the sample is solved, and the accuracy and stability of sulfur content measurement are improved.
Patent Information
- Application Number
- CN202411656703.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, when determining the sulfur content in the ternary material of lithium-ion battery, the sample is easily blown by carrier gas onto the crucible wall, resulting in incomplete combustion, low test results and low accuracy.
The sulfur content is detected by wrapping the sample with metal foil, laying the first magnetic permeability under the metal foil and covering the second magnetic permeability above, and ensuring that the sample is completely burned.
The possibility of the sample splashing on the crucible wall is reduced, the sample is burned completely, and the stability and accuracy of the test results are improved.
Abstract
Description
Technical Field
[0001] This invention relates to a method for determining the sulfur content in ternary materials for lithium-ion batteries, belonging to the field of instrumental analysis. Background Technology
[0002] Ternary lithium-ion battery materials are mainly divided into lithium nickel cobalt aluminum oxide (NCA) and lithium nickel cobalt manganese oxide (NCM), which are used as cathode materials in lithium-ion batteries. Ternary lithium-ion batteries have high energy density and good cycle performance, and are therefore widely used in new energy vehicles. Sulfur in ternary materials has significant negative effects on material performance. For example, during charge and discharge, sulfur can cause volume expansion and lattice changes in the cathode material, leading to cracks and reducing its capacity and cycle performance. Therefore, the sulfur content in the material needs to be strictly controlled.
[0003] Currently, there are many methods for testing the sulfur content in materials, such as X-ray fluorescence, heating, melting, and combustion. Among them, high-frequency combustion infrared absorption method is characterized by its speed and accuracy. This method uses a high-frequency induction furnace to burn the sample, converting the sulfur element in the sample into sulfur dioxide gas. The resulting gas mixture is then purified by passing it through a dust collection tube, drying tube, purification tube, and catalytic furnace to remove CO2 and water vapor. Finally, the sulfur dioxide-containing gas mixture enters the infrared detection system, where its content is measured using infrared absorption.
[0004] When burning samples using a high-frequency induction furnace, a T-shaped crucible is typically used, with a magnetically conductive material added as a flux (sometimes other additives are also added). Different fluxes have different effects on the sulfur content in the test sample. Currently, ferrotungsten flux is commonly used. When using ferrotungsten flux, the test results tend to be low. Furthermore, when the sample mass number is relatively large, the sample powder is easily splashed onto the crucible wall by the carrier gas during the test. The sample on the crucible wall separates from the heated magnetically conductive material, causing incomplete combustion and resulting in unstable testing, leading to problems such as low test results and low test accuracy. Resistance furnaces cover a wider heating area, but when using a carbon-sulfur analyzer with a resistance furnace, the sulfur content is usually low because ternary materials are obtained by calcining their precursor (hydroxide) and lithium source in an oxygen atmosphere (calcination temperature is generally 500~800℃). This increases the difficulty of detection, such as the lack of matching standards, or the long sulfur release time during testing, which results in a smaller integrated area when calculating the baseline, ultimately leading to lower test results. Summary of the Invention
[0005] To overcome the shortcomings of existing technologies, this invention provides a method for determining the sulfur content in ternary materials for lithium-ion batteries. It improves upon the original high-frequency combustion infrared absorption method, making it less likely for the sample to be splashed onto the crucible wall by the carrier gas.
[0006] The technical solution adopted by this invention to solve its technical problem is: A method for determining the sulfur content in ternary materials for lithium-ion batteries includes placing a sample in a T-shaped crucible and pushing it into a carbon-sulfur analyzer equipped with a high-frequency induction furnace, and detecting the sulfur content using infrared absorption. In the T-shaped crucible, the sample is wrapped with a metal foil, a first magnetic material is placed under the metal foil, and a second magnetic material is covered on top of the metal foil.
[0007] This application uses a carbon-sulfur analyzer (which consists of a high-frequency furnace and a built-in infrared cell, forming a complete set of equipment) to test the sulfur content in ternary materials. The high-frequency combustion method is adopted. First, a portion of flux is spread on the bottom of the T-shaped crucible. Then, the sample to be tested is wrapped with metal foil, and then covered with another layer of flux. During combustion, the release of sulfur elements in the sample is promoted, and incomplete combustion of the sample is avoided, thereby improving the test accuracy.
[0008] Furthermore, the metal foil wrapping the sample is folded into layers to increase the contact area with the lower first magnetic material and the upper second magnetic material.
[0009] Furthermore, the metal foil is tin foil, copper foil, or nickel foil.
[0010] Furthermore, the first magnetic material is selected from at least one of iron, nickel, copper, tin, tungsten, iron-tungsten alloy, and tungsten-tin alloy.
[0011] Furthermore, the particle size of the first magnetic material is between 10 and 30 mesh, and the sulfur content is less than 0.0005%.
[0012] Furthermore, the second magnetic material is selected from at least one of iron, nickel, copper, tin, tungsten, iron-tungsten alloy, and tungsten-tin alloy.
[0013] Furthermore, the particle size of the second magnetic material is between 10 and 30 mesh, and the sulfur content is less than 0.0005%.
[0014] Furthermore, the carbon-sulfur analyzer is calibrated with a standard substance, and a numerical relationship is established between the infrared spectral intensity value and the sulfur content of the standard substance; the calibration method is multi-point calibration or single-point calibration; the standard substance is an iron and steel standard substance.
[0015] Furthermore, the carrier gas is pure oxygen, and the flow rate is 180 L / h.
[0016] Furthermore, the integral endpoint time of the spectrum curve is 35s~300s. In the testing program, the computer determines whether the test has ended based on two criteria: first, if the test time exceeds the minimum time and the change in the spectrum curve over time is less than a certain rate (peak judgment factor); second, if the maximum test time (integration endpoint time) is reached, the test automatically ends. If the test reaches the set minimum test time but does not meet the automatic termination condition, it will continue testing until the preset maximum test time is reached, at which point it will be forcibly terminated. If the test time is less than the set minimum test time, the test meets the automatic termination condition but will not end until the test time reaches the set minimum test time.
[0017] Furthermore, the mass of the metal foil is 1% to 18% of the mass of the sample.
[0018] The beneficial effects of this invention are: the method for determining the sulfur content in ternary materials of lithium-ion batteries can reduce sample splashing onto the crucible wall and ensure complete combustion of the sample. Experiments show that the metal foil can not only cover the sample but also promote sulfur release, which can improve the stability and accuracy of the test results. The flux (magnetic material) has a layer at the bottom and surface of the metal foil, which is conducive to complete combustion of the sample and accelerates sulfur release. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure are described clearly and completely below. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are within the scope of protection of this invention.
[0020] It should be understood that, without conflict, any and all embodiments of the present invention can be combined with technical features of any other embodiment or multiple other embodiments to obtain other embodiments. The present invention includes such combinations to obtain other embodiments.
[0021] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter pertains. Where multiple definitions exist for a term, the definition herein shall prevail.
[0022] The following lists the materials used in the following embodiments and precautions for the experiments: (1) Before use, the T-type crucible (diameter × height: 26mm × 26mm, sulfur content less than 0.0005%) is placed in a muffle furnace and heated at 1200℃ for 4 hours. After cooling, it is stored in a desiccator.
[0023] (2) Oxygen: purity 99.995%.
[0024] (3) Desiccant: anhydrous magnesium perchlorate, particle size 0.7mm~1.2mm.
[0025] (4) Purifying agent: caustic soda asbestos, particle size 0.7mm~1.2mm.
[0026] (5) Flux: Tungsten-tin alloy particles (10~20 mesh), copper particles, tin particles (20~30 mesh), nickel particles (20~30 mesh), iron particles (10~20 mesh), iron-tungsten alloy particles (10~20 mesh), with a sulfur content of less than 0.0005%.
[0027] (6) Standard materials: Iron and steel standard materials (national first-class standard materials).
[0028] (7) Before testing, replace the reagents in the high-frequency induction furnace and check for leaks. Preheat the high-frequency induction furnace for more than 3 hours.
[0029] (8) Operate according to the instrument instructions. The instrument will automatically analyze and obtain test results.
[0030] (9) Calibration test: Use multi-point calibration or single-point calibration.
[0031] ① Multi-point calibration: Select four certified steel reference materials to calibrate the instrument. Choose one as the verification standard and the other three as calibration standards. The sulfur content of the verification standard should fall within the range of the sulfur contents of the three calibration standards. Perform 3 to 5 analyses on each calibration standard in the selected channel to establish a calibration curve, and then verify it using the verification standard. During sample testing, verify the results with the verification standard every 10 measurements. If the test results are outside the range, recalibrate.
[0032] ② Single-point calibration: Select two steel standard substances or standard samples. The sulfur content of the steel standard substances or standard samples should be similar to that of the sample being analyzed. Alternatively, the mass number of the sample in a single test can be controlled to ensure that the absolute value of the sulfur content in the tested material is similar to the absolute value of the sulfur content in the standard substance. Perform the single-point calibration procedure according to the instrument manual. Analyze one of the standard substances / standard samples 3 to 5 times, calculate the average value of these results, and perform systematic calibration. The average value should match the standard value and not exceed the uncertainty range given in the certificate of the standard substance / standard sample. Use the other standard substance / standard sample as the sample for analysis to verify the calibration. The analytical results should be within the uncertainty range of the standard value of the standard substance / standard sample.
[0033] (10) Determine blank value: Perform blank test before testing. That is, the test process is the same as the sample test, except that no sample is added. Other things such as flux are added in the same way.
[0034] (11) Test Procedure (High-Frequency Combustion Infrared Cell Absorption Method): A first magnetic material (nickel, copper, tin, tungsten-tin, iron-tungsten, etc.) is placed at the bottom of a T-shaped crucible. The sample to be tested is then wrapped with thin tin foil (sulfur content <0.0005%), thin nickel foil (sulfur content <0.0005%), or copper foil (sulfur content <0.0005%). A second magnetic material (nickel, copper, tin, tungsten-iron, tungsten, etc.) is then placed on its surface. The sample is then pushed into a high-frequency furnace (pure oxygen atmosphere) for combustion to obtain a mixed gas (containing CO, CO2, and other gases). The sulfur element in the tested material is converted into SO2. The mixed gas then passes through a dust collector, a water removal well test tube, a desiccant reagent tube, a purifying agent reagent tube, and a catalyst reagent tube for dust removal, drying, and purification. Finally, it enters the sulfur detection cell to detect the SO2 content and obtain the sulfur element content. Each sample is tested 3-5 times, and the relative standard error RSD is ≤4%. The average value is taken.
[0035] (12) The equipment used was an Elementrac CS-d carbon and sulfur analyzer, and the power was set to 100% during the test.
[0036] Example 1: Sample coated with tungsten-tin and copper foil + tungsten-tin Integration time 35-120 s, O2 flow rate 180 L / h. First, a blank value test was performed: 1.2-1.25 g of tungsten-tin particles were spread evenly at the bottom of the crucible. A folded 0.01 mm thick, 3 cm square copper foil was placed as the second layer, and then another layer of 1.2-1.25 g of tungsten-tin particles was placed on top. The blank value was then measured (automatically calculated by the instrument). A multi-point calibration method was used (sulfur content in steel standards was 0.0020%, 0.011%, 0.016%, and 0.0215%, with a required mass of 150-600 mg, accurate to 0.01 mg) to determine the calibration coefficient. A standard substance with a sulfur content of 0.016% (mass of 120-150 mg, accurate to 0.01 mg) was used to verify the calibration coefficient. After calibration, the sulfur content in the ternary material was tested.
[0037] Weigh 1.2–1.25 g of tungsten-tin particles and spread them evenly at the bottom of the crucible. Weigh 540–550 mg of ternary material NCA-1 (accurate to 0.01 mg), wrap it with a 0.01 mm thick, 3 cm side square copper foil, and place it as the second layer. Then, cover the sample with 1.2–1.25 g of tungsten-tin flux. Following the equipment instructions, push the sample into the high-frequency furnace combustion zone for testing. The test results are calculated by directly subtracting the blank value from the software. Three independent tests were conducted. The measured values for the three tests were 0.00984%, 0.00922%, and 0.00941%, with an average value of 0.00950%, an RSD of 3.31%, and an average test time of 45 seconds.
[0038] Comparative Example 1: Tungsten-tin + Sample + Tungsten-tin After testing the blank value and calibrating the instrument according to the method and steps of Example 1, the sulfur content in NCA-1 was detected. The sample was not covered with copper foil during the test. Three independent tests were conducted, with measured values of 0.00867%, 0.00791%, and 0.00843%, respectively. The average value was 0.00834%, the RSD was 4.66%, and the average test time was 43 seconds.
[0039] Comparing the test results of Example 1 with those of Comparative Example 1, it was found that the test results of Comparative Example 1 were lower, and the relative standard deviation (RSD) of the test results was higher than that of Example 1, indicating that adding nickel foil to the sample can improve the precision of the test.
[0040] Example 2: Sample coated with iron and nickel foil + tungsten Following the methods and steps of Example 1, blank values were tested and the instrument calibrated before detecting the sulfur content in NCA-1. During the test, the bottom flux consisted of iron particles with a mass of 0.640–0.645 g; the sample was then wrapped in a 0.01 mm thick, 3 cm square nickel foil as the second layer; the top flux consisted of tungsten particles with a mass of 1.65–1.70 g, and other parameters remained the same. Three independent tests were performed, with measured values of 0.0100%, 0.00957%, and 0.00982%, respectively, with an average value of 0.00980%, an RSD of 2.20%, and an average test time of 42 seconds.
[0041] Comparative Example 2: Iron + Sample + Tungsten After testing the blank value and calibrating the instrument according to the method and steps of Example 2, the sulfur content in NCA-1 was detected. The sample was not covered with nickel foil during the test. Three independent tests were conducted, and the measured values for the three tests were 0.00932%, 0.00854%, and 0.00891%, with an average value of 0.00892%, an RSD of 4.37%, and an average test time of 43 seconds.
[0042] Comparative Example 3: Iron + Nickel Powder + Sample + Tungsten After testing the blank value and calibrating the instrument according to the method and steps of Example 2, the sulfur content in NCA-1 was detected. During the test, an equivalent amount of nickel particles (mass equivalent to the corresponding nickel foil, 20-30 mesh, S < 0.0005%) were used to cover the sample without metal foil wrapping, and other procedures were the same. The test was performed independently three times, and the measured values of the three tests were 0.00925%, 0.00877%, and 0.00938%, with an average value of 0.00913%, an RSD of 3.52%, and an average test time of 42 seconds.
[0043] Comparing the test results of Example 2 with Comparative Examples 2 and 3, it was found that Example 2 had the highest result (0.00980%) and the lowest RSD (2.20%), indicating that coating the sample with nickel foil before testing allowed for more complete combustion. Comparing Comparative Examples 2 and 3, it was found that the test results with added nickel powder were higher than those of Comparative Example 2, and the RSD was also lower. This indicates that nickel can promote sulfur release from the sample during testing, improving the accuracy and stability of the test.
[0044] Example 3: Iron + Tin Foil Coated Sample + Tungsten Following the methods and steps of Example 2, blank values were tested, and the instrument was calibrated before detecting the sulfur content in NCA-1. During the test, the bottom flux consisted of iron particles (0.690–0.695 g by mass), and the top flux consisted of tungsten particles (1.75–1.80 g by mass). The sample was wrapped in tin foil, and all other parameters were the same. Three independent tests were performed. The measured values for the three tests were 0.0970%, 0.00986%, and 0.00954%, with an average value of 0.00970%, an RSD of 1.65%, and an average test time of 40 seconds.
[0045] Comparative Example 4: Iron + Tin Powder + Sample + Tungsten Following the methods and steps of Example 3, blank values were tested, and the instrument was calibrated before detecting the sulfur content in NCA-1. During the test, an equivalent amount of tin particles (mass equivalent to the corresponding tin foil, 20-30 mesh, S < 0.0005%) were used to cover the sample without metal foil wrapping, while other procedures remained the same. Three independent tests were performed, with measured values of 0.00915%, 0.00894%, and 0.00924%, respectively. The average value was 0.00911%, the RSD was 3.52%, and the average test time was 42 seconds.
[0046] Comparing the test results of Example 3 with those of Comparative Example 4 and Comparative Example 2, it was found that Example 3 had the highest test results and the lowest RSD, indicating that wrapping the sample with tin foil before testing allows for more complete combustion. Comparing Comparative Example 2 and Comparative Example 4, it was found that the test results with added tin particles were higher than those of Comparative Example 2, and the RSD was also lower. This indicates that tin can promote the release of sulfur from the sample during testing, improving the accuracy and stability of the test.
[0047] Example 4: Sample coated with iron and nickel foil + tungsten Following the methods and steps of Example 3, blank values were tested, and the instrument was calibrated before detecting the sulfur content in NCA-1. During the test, the bottom flux consisted of iron particles with a mass of 0.20–0.21 g; the sample mass was 600–620 mg; and the top flux consisted of tungsten particles with a mass of 1.50–1.51 g. The sample was coated with nickel foil, and all other parameters were the same. Three independent tests were performed. The measured values for the three tests were 0.00964%, 0.00952%, and 0.00977%, with an average value of 0.00964%, an RSD of 1.30%, and an average test time of 43 seconds.
[0048] Example 5: Sample coated with iron and nickel foil + tungsten Following the methods and steps of Example 4, blank values were tested, and the instrument was calibrated before detecting the sulfur content in NCA-1. During the test, the bottom flux consisted of iron particles with a mass of 0.20–0.21 g; the sample mass was 300–320 mg; and the top flux consisted of tungsten particles with a mass of 1.50–1.51 g, with all other parameters remaining the same. Three independent tests were performed. The measured values for the three tests were 0.00974%, 0.00945%, and 0.00983%, with an average value of 0.00967%, an RSD of 2.05%, and an average test time of 38 seconds.
[0049] Example 6: Samples coated with iron, tungsten, and tin foil + iron, tungsten, and tin Integration time 35-120 s, O2 flow rate 180 L / h. First, a blank value test was performed: 0.120-0.125 g of iron particles and 0.64-0.65 g of tungsten-tin particles were spread evenly at the bottom of the crucible. A 0.02 mm thick, 3 cm square tin foil was folded and placed as the second layer, and then another layer of 0.120-0.125 g of iron particles and 0.64-0.65 g of tungsten-tin particles was placed on top. The blank value was then measured (automatically calculated by the instrument). A single-point calibration method was used (sulfur content in the steel standard was 0.080%, mass number was 400-580 mg, accurate to 0.01 mg) to determine the calibration coefficient. A steel standard with a sulfur content of 0.116% (mass number was 270-400 mg, accurate to 0.01 mg) was used to verify the calibration coefficient. After calibration, the sulfur content in the ternary material was tested.
[0050] Weigh 0.120~0.125g of iron particles and 0.64~0.65g of tungsten-tin particles and spread them evenly at the bottom of the crucible. Weigh 500~640mg of ternary material NCM-1 (accurate to 0.01mg), wrap it with a 0.01mm thick square tin foil with a side length of 3cm and place it as the second layer. Then cover the sample with 0.380~0.385g of iron particles and 1.44~1.49g of tungsten-tin particles. Then push the sample into the high-frequency furnace combustion zone according to the equipment instruction manual for testing. The test results are obtained by directly subtracting the blank from the software calculation. Ten independent tests were conducted, and the measured values for the ten tests were 0.0757%, 0.0745%, 0.0763%, 0.0742%, 0.0767%, 0.0773%, 0.0751%, 0.0757%, 0.0733%, and 0.0743%, with an average value of 0.0753%, an RSD of 1.70%, and an average test time of 38 seconds.
[0051] Example 7: Samples coated with iron, tungsten-tin + copper foil + tungsten Following the methods and steps of Example 6, blank values were tested and the instrument calibrated before detecting the sulfur content in the ternary material NCM-1. During the test, the sample was wrapped in a square copper foil with a thickness of 0.01 mm and a side length of 1.5 cm and placed as the second layer; the sample mass was 50–200 mg; the top layer of flux consisted of tungsten particles with a mass of 1.50–1.51 g, and other parameters were the same. Five independent tests were conducted, and the measured values for the five tests were 0.0763%, 0.0745%, 0.0754%, 0.0735%, and 0.0767%, with an average value of 0.0751%, an RSD of 1.50%, and an average test time of 37 s.
[0052] Example 8: Sample coated with tungsten-tin and copper foil + tungsten-tin Following the methods and steps of Example 6, blank values were tested, and the instrument was calibrated before detecting the sulfur content in NCM-1. During the test, 0.60–0.65 g of tungsten-tin particles were weighed and spread evenly at the bottom of the crucible. 300–350 mg of ternary material NCM-1 (accurate to 0.01 mg) was weighed and wrapped with a 0.01 mm thick, 2 cm side square copper foil as the second layer. Then, 0.60–0.65 g of tungsten-tin flux was placed on top of the sample. The sample was then pushed into the high-frequency furnace combustion zone for testing according to the equipment instructions. The test results were calculated by directly subtracting the blank value from the software. Five independent tests were conducted. The measured values of the five tests were 0.0728%, 0.0762%, 0.0753%, 0.0748%, and 0.0760%, with an average value of 0.0750% and an RSD of 3.34%. The average test time was 45 seconds.
[0053] Example 9: Samples coated with tin, iron, and copper foil + tin, iron The sulfur content in NCM-1 was determined after testing blank values and calibrating the instrument according to the methods and procedures in Example 7. During the test, the bottom flux consisted of 0.30–0.35 g of tin particles and 0.30–0.35 g of iron particles, while the top flux consisted of 0.40–0.45 g of tin particles and 0.40–0.45 g of iron particles; all other parameters remained the same. Three independent tests were performed, with measured values of 0.0739%, 0.0745%, and 0.0761%, respectively. The average value was 0.0749%, the RSD was 2.00%, and the average test time was 36 seconds.
[0054] Example 10: Sample coated with iron and tin foil + iron The sulfur content in NCM-1 was detected after testing blank values and calibrating the instrument according to the method and steps of Example 7. During the test, the bottom flux consisted of 0.40–0.45 g of iron particles, wrapped in a 0.01 mm thick, 3 cm side square tin foil as the second layer. The top layer of flux consisted of 0.70–0.75 g of iron particles, with other parameters remaining the same. Three independent tests were performed. The measured values for the three tests were 0.0752%, 0.0775%, and 0.0744%, with an average value of 0.0757%, an RSD of 2.13%, and an average test time of 37 seconds.
[0055] Example 11 Samples coated with iron, tungsten, tin + nickel foil + iron, tungsten, tin Integration time 35-120 s, O2 flow rate 180 L / h. First, a blank value test was performed: 0.10-0.12 g of iron particles and 0.64-0.65 g of tungsten-tin particles were spread evenly at the bottom of the crucible. A 0.02 mm thick, 3 cm side square nickel foil was folded and placed as a second layer, and then another layer of 0.10-0.12 g of iron particles and 0.64-0.65 g of tungsten-tin particles was placed on top. The blank value was then measured (automatically calculated by the instrument). A single-point calibration method was used (sulfur content in the steel standard was 0.0215%, mass number was 590-620 mg, accurate to 0.01 mg) to determine the calibration coefficient. A steel standard with a sulfur content of 0.052% (mass number was 300-310 mg, accurate to 0.01 mg) was used to verify the calibration coefficient. After calibration, the sulfur content in the ternary material was tested.
[0056] Weigh 0.10-0.12g of iron particles and 0.64-0.65g of tungsten-tin particles and spread them evenly at the bottom of the crucible. Weigh 590-620mg of ternary material NCM-2 (accurate to 0.01mg), wrap it with a 0.01mm thick, 3cm square nickel foil, and place it as the second layer. Then cover the sample with 0.10-0.12g of iron particles and 0.64-0.65g of tungsten-tin particles. Then, according to the equipment instructions, push the sample into the high-frequency furnace combustion zone for testing. The test results are calculated by directly subtracting the blank from the software. Six independent tests were conducted. The measured values of the six tests were 0.0206%, 0.0216%, 0.0211%, 0.0209%, 0.0218%, and 0.0202%, with an average value of 0.0211%, an RSD of 2.23%, and an average test time of 46s.
[0057] Comparative Example 5: Combustion Test of Resistance Furnace The resistance furnace combustion infrared absorption method involves pushing a crucible (boat-shaped crucible) containing the sample into the combustion zone of the resistance furnace, where the sample burns in an oxygen stream. Under the influence of high temperature and oxygen, sulfur in the sample is converted into sulfur dioxide gas. The mixed gas first passes through the dust removal and drying tube of the resistance furnace (for dust removal and water vapor absorption), and then is introduced into a high-frequency induction furnace (used for preheating simultaneously with the resistance furnace) for further purification, including dust removal, drying, purification, and catalytic furnace processes to remove CO2 and water vapor. Finally, the sulfur dioxide-containing mixed gas enters the infrared detection system, where its content is measured using infrared absorption. Before testing, the instrument also requires reagent replacement, preheating, blank value measurement (empty crucible test), and calibration.
[0058] A single-point calibration method was used (the sulfur content in the steel standard was 0.0215%, the mass number was 590~620mg, and the accuracy was 0.01mg) to determine the calibration coefficient. A steel standard with a sulfur content of 0.052% (mass number was 300~310mg, and the accuracy was 0.01mg) was used to verify the calibration coefficient. After calibration, the sulfur content in the ternary material was tested.
[0059] 590~620mg of ternary material NCM-2 was placed directly into a porcelain boat crucible with a length × height of 88mm × 10mm and spread out. Then it was pushed into the combustion zone of the resistance furnace, the furnace door was closed and the test was started. The measurements of the 6 tests were 0.0198%, 0.0195%, 0.0203%, 0.0206%, 0.0194% and 0.0185%, respectively, with an average value of 0.0197, an RSD of 3.77%, and an average test time of 55s.
[0060] Comparing Example 11 with Comparative Example 5, it was found that the measured value of Comparative Example 5 was slightly lower. This is because when using a resistance furnace for testing, the testing time is relatively long, which may lead to a smaller integrated area when calculating the baseline.
[0061] The method described in this application requires no complex sample preparation, resulting in a simple, stable, and reliable testing process. During testing, the sample is wrapped with tin foil, nickel foil, or copper foil to reduce sample splashing onto the crucible wall and ensure complete combustion. Tin foil, nickel foil, and copper foil not only cover the sample but also promote sulfur release, improving the stability and accuracy of the test results. The use of magnetically conductive materials (such as nickel, copper, tin, tungsten-tin, iron-tungsten, etc.) placed on top of and below the metal foil further facilitates complete combustion and accelerates sulfur release.
[0062] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with the embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0063] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for determining the sulfur content in a lithium-ion battery ternary material, comprising placing a sample in a T-shaped crucible, pushing the sample into a carbon-sulfur analyzer with a high-frequency induction furnace, and detecting the sulfur content by infrared absorption method, characterized in that: In the T-shaped crucible, the sample is wrapped by a metal foil, a first magnetic conductive material is laid under the metal foil, and a second magnetic conductive material is covered above the metal foil.
2. The method for determining the sulfur content in the ternary material of a lithium-ion battery according to claim 1, characterized in that: The metal foil is tin foil, copper foil or nickel foil.
3. The method for determining the sulfur content in the ternary material of a lithium-ion battery according to claim 1, characterized in that: The first magnetic conductor is selected from at least one of iron, nickel, copper, tin, tungsten, iron-tungsten alloy, and tungsten-tin alloy.
4. The method for determining the sulfur content in the ternary material of a lithium-ion battery according to claim 3, characterized in that: The particle size of the first magnetic conductor is between 10 mesh and 30 mesh, and the sulfur content is less than 0.0005%.
5. The method for determining the sulfur content in the ternary material of a lithium-ion battery according to claim 1, characterized in that: The second magnetic conductor is selected from at least one of iron, nickel, copper, tin, tungsten, iron-tungsten alloy, and tungsten-tin alloy.
6. The method for determining the sulfur content in the ternary material of a lithium-ion battery according to claim 5, characterized in that: The particle size of the second magnetic conductor is between 10 meshes and 30 meshes, and the sulfur content is less than 0.0005%.
7. The method for determining the sulfur content in lithium-ion battery ternary materials according to claim 1, characterized in that: The carbon-sulfur analyzer is calibrated with standard substances, and a numerical relationship between the infrared spectrum intensity value and the sulfur content of the standard substance is established; the calibration method is multi-point calibration or single-point calibration; the standard substance is a steel standard substance.
8. The method for determining the sulfur content in lithium-ion battery ternary materials according to claim 1, characterized in that: The carrier gas is pure oxygen with a flow rate of 180 L / h.
9. The method for determining the sulfur content in lithium-ion battery ternary materials according to claim 1, characterized in that: The end point time of spectrum curve integration is 35s~300s.
10. The method for determining the sulfur content in lithium-ion battery ternary materials according to claim 1, characterized in that: The mass of the metal foil is 1% to 18% of the mass of the sample.
Citation Information
Patent Citations
Method for detecting content of sulfide in steel
CN106645007A
Detection method for quickly evaluating relative content of residual alkalis on surface of ternary positive electrode material
CN108956850A
Method for measuring content of sulfur in ternary precursor
CN113176252A